134k views
5 votes

- (1)/(3) (9x + 42) - 5x = - 70
Can someone help me please!!!


User Belun
by
5.9k points

2 Answers

7 votes
For the statement to be true, x is 7
User Eggonlegs
by
6.4k points
6 votes

Answer:

x = 7

Explanation:


- (1)/(3) (9x + 42) - 5x = - 70

Multiply the terms in the bracket

We have

- 3x - 14 - 5x = - 70

- 8x - 14 = - 70

Using the addition property, add 14 to both sides

That's

- 8x + 14 - 14 = - 70 + 14

- 8x = - 56

Divide both sides by - 8

That's


( - 8x)/( - 8) = ( - 56)/( - 8)

We have the final answer as

x = 7

Hope this helps you

User Dave Cribbs
by
6.1k points